2021
DOI: 10.5339/qmj.2021.55
|View full text |Cite
|
Sign up to set email alerts
|

Tension Pneumomediastinum: A life-threatening condition in patients with COVID-19

Abstract: Tension pneumomediastinum (TPM) is a rare but potentially fatal clinical entity. TPM leads to the leakage of air into the mediastinal cavity and increased pressure in thoracic vessels, respiratory tract, and the heart. Herein, this report presents a series of five cases of coronavirus disease-2019 (COVID-19) that caused acute respiratory distress syndrome (ARDS) and TPM. All patients were male who had severe ARDS with a secondary lung infection that required invasive ventilation and had moderate positive-end e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Its prevalence, risk factors, and final outcome remain unclear. 13,14,[30][31][32][33][34][36][37][38][39] Our research contributes to understanding the combination of SP, SPM and COVID-19 in non-ventilated patients, and quantifying their associated risks for in-hospital mortality.…”
mentioning
confidence: 95%
“…Its prevalence, risk factors, and final outcome remain unclear. 13,14,[30][31][32][33][34][36][37][38][39] Our research contributes to understanding the combination of SP, SPM and COVID-19 in non-ventilated patients, and quantifying their associated risks for in-hospital mortality.…”
mentioning
confidence: 95%
“…Shaikh et al reported five patients with COVID-19 ARDS on mechanical ventilation on moderate positive end-expiratory pressure (PEEP) who developed tension pneumomediastinum [32]. In this series, two patients required chest drain to relieve the tension, one patient was managed with extracorporeal membrane oxygenation (ECMO) because of severe ARDS, and two patients died eventually.…”
Section: Discussionmentioning
confidence: 85%
“…The chi-square [ 2 ] test and the Fisher exact test will be used to evaluate categorical data, if appropriate. The unpaired ‘ t ’ or Mann–Whitney U test will be used to compare continuous variables (quantitative data) between the 2 independent groups.…”
Section: Methods: Data Collection Management and Analysismentioning
confidence: 99%
“…Studies have revealed that COVID 19 virus utilizes the angiotensin converting enzyme, a protein expressed on the surface of many cells including respiratory mucosal epithelium, as a port of entry. [1][2][3] Angiotensin-converting enzyme-2 is normally secreted in upper and lower respiratory epithelial cells; thus, angiotensin-converting enzyme-2 stimulation in COVID-19 infection will significantly surge pro-inflammatory mediators and mucosal secretions, leading to dyspnea (breathlessness), cough, and throat pain. [4,5] This protein also acts as a pro-inflammatory mediator, which contributes to increased respiratory secretions in respiratory infections, and some of the other symptoms, predominantly, dyspnea, cough, and throat pain.…”
Section: Introductionmentioning
confidence: 99%